Enhanced performance based on a hybrid cathode backing layer using a biomass derived activated carbon framework for methanol fuel cells. (10th October 2017) - Balakrishnan, Prabhuraj; Inal, I. Isil Gurten; Cooksey, Emily; Banford, Anthony; Aktas, Zeki; Holmes, Stuart M.
Graphical abstract: Illustration of enhanced power performance attributed to the usage of activated carbon. Highlights: Activated carbon prepared from factory waste-tea possessed 75.69% of mesopores and 24.31% of micropores. Activated carbon used as cathode microporous layer, improved gas permeability and water removal characteristics. The activated carbon improved fuel cell performance by 33% and enhanced stability, when tested in general operating conditions. Abstract: Direct methanol fuel cells (DMFCs) suffer from performance reduction due to mass transport losses incurred at high current regions. In this work, we report the use of activated carbon (AC), prepared from factory waste-tea, as cathode microporous layer in the membrane electrode assembly (MEA) of a DMFC, alleviating this mass transport effect. This biomass based AC framework, when tested under fuel cell operating conditions provided 0.25 V @ 300 mA cm −2, enhancing cell performance by 33% over standard electrodes at 70 °C. During uninterrupted durability testing, this electrode displayed exceptional stability in mass transport dominated region, with loss of 15 mV day −1, compared to 25 mV day −1 loss for the standard. Sample and electrode characterization measurements reveal that pore size distribution/particle size characteristics coupled with hydrophobic nature of the synthesized activated carbon, contributed to the performance improvement.